Does Analysis Matter? Economics and Planning in the Department of the Interior - Farrow, Robert (The Review of Economics and Statistics, 1991)
Economics is the basis for a substantial portion of the formal policy analyses conducted in government though the effect of analysis is seldom investigated. The 5-Year Offshore Leasing Plan of the Department of the Interior is the specific basis for a schedule of auctions in each of twenty-six planning areas. The schedule is investigated for its relationship to data presented in the plan using a Poisson regression. The conclusion is that the data are statistically related to the number of sales, but that estimated coefficients are of such small size that only major changes in the data would alter the outcome. Copyright 1991 by MIT Press.